Anomalous origin of the right coronary artery from the pulmonary artery associated with an aortopulmonary window - Padebettu Subramanya Seetharama Bhat; Chandana Nirmala Chandrashekar; Divya Mallikarjun; S L Girish Gowda (Wolters Kluwer Medknow Publications, 2018)
Anomalous origin of the right coronary artery (RCA) from the pulmonary artery is a rare entity that causes chronic left-to-right shunting of blood from the RCA, through the coronary collaterals into the pulmonary artery. This results in persistent myocardial ischemia and ventricular dysfunction. Association of this anomaly with an aortopulmonary window worsens the condition further due to an additional shunt. We encountered a combination of these two anomalies along with an ostium secundum atrial septal defect in a 10-month-old baby who presented with excessive crying and failure to thrive. Evaluation by transthoracic echocardiography and cardiac computed tomography scan confirmed the diagnosis. Intrapulmonary baffle was done using a pericardial patch to connect the RCA origin to ascending aorta through the aortopulmonary window, similar to Takeuchi procedure. Concomitantly, ostium secundum atrial septal defect was also closed.